Application of text-based math braille translation software in learning mathematics - Wiraman Niyomphol (2018)
This research project involves the development of a text-based math Braille translation software to support learning in mathematics. The researcher collected 192 math symbols from Nemeth Braille code resources. Nemeth code was used as the basis of text-based math symbols design for regular print text entry in any text editor. The math translation software was developed to convert these text-based math symbols to Braille. This software can be interfaced to Braille software for other languages. The software was tested for its performance with 10 subjects who are math teachers and material production staff in Thailand. They were given 3 hours of training on the use of the software and 2 hours to work on an exercise. Overall performance of the exercise was 95.32 percent accuracy. Based on the questionnaire after the exercise, overall satisfaction level of using this method was between the range of "acceptable and "good". A follow-up interview reflects the opinion that this method would be most appropriate for math teachers and material production staff who are not familiar with Braille. This software would provide greater access toward math education of children with visual impairment. © Common Ground, Wiraman Niyomphol, Pintip Ruenwongsa.